DETECTION OF SHIGELLA SP ON STOOL CHILDREN WITH DIARRHEA USING CULTURE METHODE AND PCR - Rusdianto Rusdianto; Muh Nasrum Massi; Ahyar Ahmad (Faculty of Medicine, Hasanuddin University., 2016)
ABSTRACT Introduction: Diarrhea is one health problem in the world with mortality and morbidity rates are high, both in developed and developing countries. This research aims to detect Shigella sp in the stool of children with diarrhea using culture method and PCR. Methods: This research is a descriptive with cross-sectional design. A total of 50 samples were obtained from four health centers in Makassar city, i.e Barabaraya, Pampang, Antang Perumnas and Tamangapa from May - July 2016 with rectal swab method. For culture test, the samples were inoculated on medium SSA. While with PCR test, primer icsA (526 bp) was used. Results: The results indicate that, from 50 samples tested by using culture method, there is no sample (0%) posi- tive detected Shigella sp. While the PCR method there 6 samples (24%) positive detected Shigella sp. Conclusion: The sensitivity of PCR in the detection of Shigella sp from the level of dilution 100 - 10-3. Al together, it can be inferred that PCR method is more accurate method detect Shigellasp than other culture methode. Keywords: Diarrhea, Shigellasp, Culture, PCR